2018
DOI: 10.1002/adfm.201800700
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Nanostamping with Spongy Mesoporous Silica Stamps

Abstract: Classical microcontact printing involves transfer of molecules adsorbed on the outer surfaces of solid stamps to substrates to be patterned. Spongy mesoporous silica stamps are prepared that can be soaked with ink and that are topographically patterned with arrays of submicron contact elements. Multiple successive stamping steps can be carried out under ambient conditions without ink refilling. Lattices of fullerene nanoparticles with diameters in the 100 nm range are obtained by stamping C 60 /toluene solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…In a first report, they set out a process to synthesize porous stamps by molding them against a macroporous silicon master. 35 The resulting porous stamps were attached onto 3 mm thick PDMS films connected to a steel holder. The porosity of the stamp allowed ideal imbibition of a C 60 ink in toluene onto perfluorinated glass or 1-dodecanethiol on gold-coated glass.…”
Section: Towards High-throughput Size Controllable and Depletion-free...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a first report, they set out a process to synthesize porous stamps by molding them against a macroporous silicon master. 35 The resulting porous stamps were attached onto 3 mm thick PDMS films connected to a steel holder. The porosity of the stamp allowed ideal imbibition of a C 60 ink in toluene onto perfluorinated glass or 1-dodecanethiol on gold-coated glass.…”
Section: Towards High-throughput Size Controllable and Depletion-free...mentioning
confidence: 99%
“…Stamping needs to be interrupted after a limited number of stamping steps to reload the ink on the elastomeric stamps. To this aim, similar to the abovementioned concepts of silicon-based SPTs and NFBs, the porous polymeric stamps obtained by micromolding can be engineered to obtain ink reservoirs in the bulk of the polymer, 35,36 facilitating the continuous deposition of inks imbibed into the polymeric matrix. This approach has resulted in the recently developed capillary stamping, 37 a methodology in which elastomeric stamps, prepared with protocols similar to PPL, are prepared with a porous polymeric stamping layer, allowing for a continuous ink reservoir.…”
Section: Caterina Alfanomentioning
confidence: 99%
“…[ 11–13 ] While traditional flexography plates are based on solid elastomers, recent work has revealed promise for advancing relief printing with more sophisticated material design. For example, capillary‐based contact stamps have been fabricated using mesoporous silica to achieve submicron patterning of fullerenes and polymers, [ 14 ] and further refined with porous polymers to achieve compatibility with the automated polymer pen lithography approach. [ 15 ] Using a nanoporous transfer medium fabricated from carbon nanotube forests, Kim et al demonstrated precision patterning of thin films for electronics, achieving sub‐100 nm film thickness and sub‐5 μm resolution with high fidelity.…”
Section: Figurementioning
confidence: 99%
“…Smooth Si wafer pieces and tpSi pieces with areas of 0.5×0.5 cm 2 were coated with a 35 nm thick gold layer using a Balzers BAE 120 evaporator following protocols reported elsewhere. 48 For this purpose, the tpSi and smooth Si wafer pieces were glued on glass slides with double-sided adhesive tape and placed in the vacuum chamber above the gold source at a distance of 25 cm. The chamber pressure was set to 10 -4 mbar, the current was set to 4.20 A, and the baffle was removed for gold deposition.…”
Section: Sers Performance Of 3d Gold Nanodendrite Layersmentioning
confidence: 99%